Integrative Proteomic and MicroRNA Analysis: Insights Into Mechanisms of Eyestalk Ablation-Induced Ovarian Maturation in the Swimming Crab Portunus trituberculatus - Meng, Xianliang; Zhang, Mengqian; Gao, Baoquan; Lv, Jianjian; Li, Jian; Liu, Ping (Frontiers in Endocrinology, 2020)
Eyestalk ablation is the most common method to induce ovarian maturation in decapod crustacean aquaculture, but it jeopardizes broodstock survival and larvae production. It is important to understand the molecular basis underlying the maturation triggered by ablation, and thereby develop an alternative measure for maturation manipulation. In this study, we investigated alterations of ovarian proteome and miRNA profile after ablation in a commercially important marine crab Portunus trituberculatus. Quantitative proteomic analysis using iTRAQ revealed that 163 proteins were differentially expressed following ablation, and modulation of methyl farnesoate metabolism and activation of calcium signaling may play important roles in the ovarian maturation induced by ablation. miRNA expression profiling identified 31 miRNAs that showed statistically significant changes. Integration of miRNA and proteome expression data with miRNA target prediction algorithms, generated a potential regulatory network consisting of 26 miRNAs and 30 proteins linked by 71 possible functional associations. The miRNA-protein network analysis implied that miRNAs may be involved in controlling expression of proteins related to methyl farnesoate synthesis, calcium signals, and energy metabolism. Experimental validation indicated that multiple miRNAs act synergistically to regulate expression of Farnesoic acid O-methyltransferase and Calmodulin. Our findings provide new insights for elucidating the mechanisms underlying eyestalk ablation induced ovarian maturation, and could be useful for devising an alternative technique for manipulating reproduction in P. trituberculatus and other decapods.This is a provisional file, not the final typeset article